2015
DOI: 10.1039/c4fo00723a
|View full text |Cite
|
Sign up to set email alerts
|

Development of food-grade nanoemulsions and emulsions for delivery of omega-3 fatty acids: opportunities and obstacles in the food industry

Abstract: Consumption of biologically active amounts of omega-3 fatty acids is linked to improved human health, which has partly been attributed to their important role in brain development and cardiovascular health. Western diets are relatively low in omega-3 fatty acids and many consumers turn to supplements or functional foods to increase their intake of these healthy lipids. Fish oil is one of the most widely used sources of omega-3 fatty acid for supplementation and has greater health benefits than plant sources be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(135 citation statements)
references
References 117 publications
1
129
0
Order By: Relevance
“…97 Numerous in vitro and in vivo studies have shown that delivering these bioactive agents within nanoparticles (rather than within larger particles or in bulk phases) can greatly increase their bioavailability. For example, nanoemulsions have been shown to increase the bioaccessibility or bioavailability of carotenoids, 128 curcumin, 129 coenzyme Q10, 130,131 ω-3 fatty acids, 132 and fat-soluble vitamins. 133 There are a number of different physicochemical mechanisms that may be responsible for this improvement.…”
Section: Potential Mechanisms Of Action Of Nanoparticle Toxicitymentioning
confidence: 99%
“…97 Numerous in vitro and in vivo studies have shown that delivering these bioactive agents within nanoparticles (rather than within larger particles or in bulk phases) can greatly increase their bioavailability. For example, nanoemulsions have been shown to increase the bioaccessibility or bioavailability of carotenoids, 128 curcumin, 129 coenzyme Q10, 130,131 ω-3 fatty acids, 132 and fat-soluble vitamins. 133 There are a number of different physicochemical mechanisms that may be responsible for this improvement.…”
Section: Potential Mechanisms Of Action Of Nanoparticle Toxicitymentioning
confidence: 99%
“…The free fatty acids released from lipid digestion contributed to formation of anionic species that further increased the negative charge (Salvia‐Trujillo, Qian, Martin‐Belloso, & McClements, 2013a). However, the fish oil emulsion showed a relatively lower zeta potential after digestion, which was possibly because that the free fatty acids were not fully released as a result of its low degree of lipolysis under intestinal conditions (Komaiko, Sastrosubroto, & McClements, 2016; Walker, Decker, & McClements, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, LCT forms mixed micelles with relatively large hydrophobic domains suitable to deliver beta‐carotene (Zhang et al., 2016). However, the bioaccessibility of fish oil carried beta‐carotene was significantly lower than corn oil or palm oil, which was probably because of its special lipid composition (Komaiko et al., 2016; Ulven et al., 2011; Walker et al., 2015). Qian et al., (2012b) applied orange oil abundant of short‐length carbon chain to form beta‐carotene nanoemulsion, in which the bioaccessibility of beta‐carotene was close to zero.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of algae oil into foods using nanoemulsion has the potential to improve LC3PUFA bioavailability (7) . However, nanoemulsion may also affect the shelf life of foods as increased droplet surface areas may lead to lipid oxidation (8) .The aim of the present single-blinded sensory evaluation study was to determine whether study participants (n = 62) could detect differences when an algae oil nanoemulsion was integrated with a strawberry yogurt and tasted after storage over 2, 9 and 16 days at 4°C. All samples were prepared using breakfast drinking yogurt, natural sweetener and strawberry flavouring.…”
mentioning
confidence: 99%
“…The incorporation of algae oil into foods using nanoemulsion has the potential to improve LC3PUFA bioavailability (7) . However, nanoemulsion may also affect the shelf life of foods as increased droplet surface areas may lead to lipid oxidation (8) .…”
mentioning
confidence: 99%